Challenges in Diagnosing Intrahepatic Cholangiolithiasis in a 39-Year-Old Patient - A. K. Guseva; O. N. Sergeyeva; T. P. Nekrasova; O. T. Imaraliev; A. V. Okhlobystin; Y. N. Shirokova; A. S. Ostrovskaya; M. S. Zharkova; A. S. Cherenda; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to highlight the challenges of diagnosing and treating a patient with severe intrahepatic cholangiolithiasis.Key points. Primary sclerosing cholangitis is a chronic progressive liver disease characterized by destructive inflammation and fibrosis in the bile ducts, leading to biliary strictures, secondary biliary cirrhosis, portal hypertension and liver failure. Cholangiolithiasis occurs in more than half of cases of primary sclerosing cholangitis and can be both a complication and a cause of secondary sclerosing cholangitis, maintaining inflammation in the ducts and facilitating stone formation. Genetic mutations are known to contribute to the development of gallstones in young patients, including low phospholipid-associated cholelithiasis. Despite the wide range of modern methods of radiological and endoscopic diagnostics, there are still difficulties in differential diagnostics of bile duct diseases. This article presents a clinical case of a 39-year-old male patient with primary sclerosing cholangitis, dyslipidemia and multiple cholangioliths in the gallbladder, intraand extrahepatic bile ducts.Conclusion. The presented clinical case demonstrates the difficulties in assessing pathogenesis, choosing diagnostic and therapeutic approaches in patients with severe intrahepatic lithiasis that may mimic hepatic neoplasm. Combination of non-invasive and endoscopic methods, such as magnetic resonance imaging, magnetic resonance cholangiopancreatography, endoscopic retrograde cholangiopancreatography, and cholangioscopy, appears to be the most effective both diagnostically and therapeutically.